Isolation and characterization of vibrio spp. from surface water in Dhaka city - Qazi, Raghib Mubassir (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2019.